Могильник Карів-І в контексті етнічних і культурних явищ останньої чверті ІІ ст. н. е. на території Західного Побужжя і верхнього Подністров'я - Онищук, Я.І. (Археологія, 2022)
У статті схарактеризовано етнокультурну ситуацію в басейнах Західного Бугу та Верхнього Дністра
в першій половині І тис. н. е. В її основі лежать процеси, пов’язані з послідовним проживанням на цих
землях населення пшеворської та вельбарської культур, а також із появою в останній чверті ІІ ст.
н. е. нової поліетнічної групи типу Карова. The article characterizes the ethnocultural situation in the basins of the Western Buh and the Upper Dnister Rivers of the last
quarter of the II century AD. It is based on cultural situation associated with the consistent residence in these areas of the
population of Przeworsk and Wielbark cultures, as well as the appearance of new polyethnic group such as Kariv in the last
quarter of the second century AD. The “Kariv group” is currently represented by a cremation burial ground on the site Kariv-I
in the Chervonohrad district of Lviv Oblast, and by single burials sites in Rechychany and Slovita near Lviv in Western Ukraine
and by a number of accidental single finds. The community of the “Kariv group” can be characterized as a mix of Przeworsk,
Suebian, Western Baltic and possibly Venedian cultural elements. It can be clearly seen both in the nature of how the graves
were constructed and in the ritual actions connected with the burial itsel. The existing dating material (fibulae, spurs, drinking
horn tips, amphorae, glass and bronze vessels, etc.), most of which comes from the closed complexes of the Kariv site, allows
us to determine the chronology of the Kariv group to the second half of the second century CE, or phase B2/C1. Its appearance
can be related to the events of the Marcomannic Wars in the Middle Danube region. The wars were attended by various ethnic
groups from the territory of the European Barbaricum, including the northern tribes of the Lombards, Chauci and others. As
a result of the difficult political and economic conditions, after they were defeated in the war, some members of the barbaric
coalition could have left the area near the Danube limes and moved to the north to the territory of more peaceful regions of the
European Barbaricum. The disappearance or assimilation of the “Kariv group” population chronologically matches the arrival of
the Wielbark culture in the Western Buh and Podollian areas.